Leadership in Changing Times : How Adaptive Leadership is Replacing Classic Leadership in a Post-Pandemic World - Tariq Khan (Karachi Liberty Publishing, 2022)
Peels back the layers of the leadership 'onion' to determine whether leading during changing times is really complicated or if we are simply making it complicated. The book includes ten case studies, anecdotes, quotes, stories, and examples from the author's experience as a leader in the corporate world and as an entrepreneur.
Including Appendix and Glossary
Keywords: Leadership -- Covid-19 -- Business -- How the COVID-19 pandemic is changing business